Moderating Styles: Understanding Diverse Techniques for Investigating the Root Cause of Use Events. (September 2018) - Tippey, Kathryn G.; McGrath, Larry S.; Yovanoff, Mary; Sneeringer, Peter
This article explores how a moderator's style shapes the techniques they use for conducting usability testing on medical devices. Different moderating styles offer distinct routes to arrive at analogous root-cause data when the moderator is appropriately trained. We interviewed three moderators from a human factors medical device consulting company about how they approach investigating the root cause of use events. A typology of three styles emerged from the interviews: Direct Moderator, Indirect Moderator, and Social Moderator. No style was inherently superior. Each moderator employs a distinct toolkit to gain insights about users' interactions with devices. These data provide product developers with either recommendations for device improvements or with documentation for human factors FDA validation.Moderators may gain from learning about alternate moderating styles to enhance their mental flexibility during testing sessions. Knowledge of various styles also encourages a more diverse set of practitioners to enter the human factors field.